Effect of the Oral Administration of Common Evening Primrose Sprout (Oenothera biennis L.) Extract on Skin Function Improvement in UVB-irradiated Hairless Mice - Hoon Kim; Soon Yeong Park; Dae Kyun Chung (MDPI AG, 2021)
Most of the studies on common evening primrose (Oenothera biennis L.) are focused on its oils (isolated from seed, root, and stem tissues). We aimed to investigate the effect of the oral administration of OBS-E on the improvement of skin function in skin-damaged hairless mice exposed to excessive ultraviolet B (UVB) radiation owing to the preliminary in vitro findings regarding the antioxidant, anti-wrinkle, and skin moisturizing activities of OBS-E. OBS-E administration for 14 weeks did not significantly affect the body weight or clinical signs. Significant reductions were observed in wrinkle parameters (area, number, length, and depth, and metalloproteinase levels) in OBS-E-administered mice compared with those in UVB-irradiated control mice. OBS-E significantly increased skin elasticity and hyaluronic acid content, but it significantly decreased transepidermal water loss. Histomorphometrical analysis revealed that OBS-E significantly reduced the epidermal thickness, area of the collagen-occupied region, and number of microfolds and inflammatory and mast cells. These results demonstrate that OBS-E can effectively enhance skin functions in terms of ameliorating wrinkle formation, promoting skin-moisturization, enhancing skin barrier function, and inhibiting inflammatory reactions. The obtained results provide good starting point for the continuation in the process of developing new inner beauty products based on OBS-E.